Profesionalisme Guru Dalam Persepsi Guru MA dan SMA: Studi Kasus di Provinsi Riau - Rian Vebrianto; Alaniyah Syafaren; Riki Apriyandi Putra (Bedelau: Journal of Education and Learning, 2020)
Teachers in the educational context have a very important and strategic role. A teacher is required to be a professional teacher. The State will provide good financial for professional teachers who got the certification. For that in this study, researchers want to cover deeply into professional teachers. Using a qualitative approach with in-depth interview method. Respondens in this research are  two teachers at the same level in the senior high school. the current question there are results that match the purpose of this study. The results from the interviews a teacher should have good skills in preparing intrument learning and implementation in teaching and learning system. Before the teacher becomes a professional teacher a teacher should at least collect portfolio himself or following the training PLPG for perapring test of professional teacher standard. The government, it is expected that more and more teachers in Indonesia quickly and appropriately to be called "Professional Teachers".